Exploring Manipulative Traits in Veronica Roth’s Divergent Novel - Ivan Yosua Perangin Angin; Thohiriyah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Roth’s novel Divergent depicts a dystopian society where faction-based identities determine social roles. Using a qualitative descriptive analysis approach, this study explores the character of Peter Hayes, an antagonist whose actions reflect deliberate psychological manipulation. This study uses E. Dotsenko's theory of manipulation. In this study, Peter only employs 4 of 6 traits, consisting of operational object manipulation, conventional manipulation, inference-oriented manipulation, and personality structure manipulation. The data was gathered from dialogues and narratives between Peter and other characters in the novel. The study findings show that Peter consistently uses negative manipulation to achieve what he wants. This article also explores how Peter's manipulative behaviour impacts the other characters and the group represented by the faction. This study contributes to young adult literature discourses by showing how antagonistic characters reflect deeper psychological and social issues. It offers insights into the intersection of literature and psychology and underscores how manipulative dynamics in fiction can shape readers’ views of power, morality, and relationships.